2020
DOI: 10.14218/jcth.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Thrombocytopenia in Chronic HCV Infection: A Review

Abstract: A large proportion of patients with chronic hepatitis C have associated thrombocytopenia (TCP). Due to bleeding risks, TCP, when severe, can limit diagnostic and therapeutic procedures, treatments, and increases risk of complications, especially excessive bleeding. It is important to understand the mechanisms that cause TCP in order to manage it. In general, TCP can be due to increased destruction or decreased production. Proposed mechanisms of increased destruction include autoantibodies to platelets and hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 47 publications
1
29
1
Order By: Relevance
“…Another mechanism might be the increased level of thrombopoietin after effective anti‐HBV treatment, which was thought to be related with improving synthetic liver function. Although an amelioration of virus‐induced immunological mechanisms might be one of the reasons in HCV patients, and there had limited evidence in HBV patients 23 …”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism might be the increased level of thrombopoietin after effective anti‐HBV treatment, which was thought to be related with improving synthetic liver function. Although an amelioration of virus‐induced immunological mechanisms might be one of the reasons in HCV patients, and there had limited evidence in HBV patients 23 …”
Section: Discussionmentioning
confidence: 99%
“…6,27 As discussed earlier, multiple factors, including potentially reduced thrombin production when platelet counts are <50 × 10 9 /L, 4 contribute to the possibility of increased bleeding risk in CLD patients. [1][2][3] Studies have identified that the risk of procedure-related bleeding is increased when platelet counts fall below approximately 60 to 75 × 10 9 /L, with the highest risk of bleeding occurring when the platelet count is <10 to 20 × 10 9 /L. [28][29][30] In general, CLD patients with platelet counts < − 50 × 10 9 /L are considered to be at high risk for procedurerelated bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with thrombocytopaenia associated with chronic liver disease (TCP-CLD) are at risk for both thrombotic and haemorrhagic complications given the complex, altered balance between thrombosis and bleeding in this patient population. [1][2][3] TCP is a reflection of the severity of CLD and contributes to the potential increased risk of bleeding in CLD patients in conjunction with the interplay between multiple elements in the haemostatic system such as platelet dysfunction, anti-platelet antibodies, platelet sequestration and destruction related to hypersplenism, myelosuppression, and alterations in haematopoietic and coagulation factors. [1][2][3] For example, the risk of bleeding in CLD may be affected by decreased thrombin production when platelet counts fall below approximately 50 × 10 9 /L, 4 yet this is countered by an increase in von Willebrand factor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations